2020
DOI: 10.1177/1043454220966831
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Timing of a Central Line Associated Bloodstream Infection Onset in Children with Cancer

Abstract: Purpose: The purpose of this study is to identify controllable treatment-environment-related factors affecting the timing of a central line-associated bloodstream infection (CLABSI) onset in children with cancer with central venous catheters (CVC). Design: This study is a secondary data analysis with the data extracted from electronic medical records in a tertiary hospital in South Korea. This study was conducted by reviewing electronic medical records of 470 pediatric cancer patients younger than the age of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Duplicates and articles not published in English were removed, and 2013 articles underwent title and abstract screening. Of these, 167 underwent full-text review and 23 studies were identified that met the inclusion criteria 10–31. All studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicates and articles not published in English were removed, and 2013 articles underwent title and abstract screening. Of these, 167 underwent full-text review and 23 studies were identified that met the inclusion criteria 10–31. All studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic antibiotics were given in four studies (one with haematological disease only and three with solid and haematological malignancies) 16–18 23. Antibiotics were explicitly stated as not given in two studies (both haematological malignancies only) 10 19.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with high-risk leukemia and those undergoing HSCT, this timing corresponds with periods of peak mucosal injury following receipt of chemotherapy and an increased risk of bacteremia (Bowen et al, 2019; Donohoe et al, 2018). Prior studies suggest that the complex transfusion needs patients experience during periods of prolonged myelosuppression are associated with an increased risk of infection (Kelly et al, 2011; Park et al, 2021). Although the need for more frequent blood product transfusions is often associated with increased manipulation of the line, it may also be a marker of compromised hemostasis and an underlying pathophysiologic context in which MBI and non-MBI organisms may more easily translocate into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…They have only been described in patients, hence, in cases in which CVC manipulation was more frequent, and their duration was also longer. Frequent manipulations, blood draws, infusions, and the time that the CVC is being used are variables frequently related to these complications in other series (8).…”
Section: Size (Fr) Length (Cm) Pmentioning
confidence: 99%
“…Although the adverse events related to central venous lines are not infrequent in pediatric patients, they have mainly been described in patients with several prothrombotic conditions at the time of the events or at high risk of infection (6)(7)(8). For instance, intensive care or oncology patients.…”
Section: Introductionmentioning
confidence: 99%